Measuring Athletic Mental Energy (AME): Instrument Development and Validation - Lu, Frank J. H.; Gill, Diane L.; Yang, Cynthia M. C.; Lee, Po-Fu; Chiu, Yi-Hsiang; Hsu, Ya-Wen; Kuan, Garry (Frontiers in Psychology, 2018)
Although considerable research indicates that mental energy is an important factor in many domains, including athletic performance (Cook & Davis, 2006), athletic mental energy (AME) has never been conceptualized and measured. Therefore, the aim of this study was to conceptualize and develop a reliable and valid instrument to assess athletic mental energy. In Study 1, a focus group interview established the initial framework of athletic mental energy. Study 2 used a survey to collect athletes’ experiences of athletic mental energy and develop a scale draft titled “Athletic Mental Energy Scale (AMES).” In Study 3, we examined the psychometric properties and the underlying structure of AMES via item analysis, internal consistency, and exploratory factor analysis (EFA). In Study 4, we used confirmatory factor analysis (CFA) to examine AMES’s factorial validity; and examined concurrent and discriminant validity by examining correlations with athletes’ life stress, positive state of mind, and burnout. In study 5, we examined the measurement invariance of the 6-factor, 18-item AMES with Taiwanese and Malaysian samples. Study 6 examined the predictive validity by comparing AMES scores of successful and unsuccessful martial artists. Across these phases, results showed a 6-factor, 18-item AMES had adequate content validity, factorial structure, nomological validity, discriminant validity, predictive validity, measurement invariance, and reliability. We suggest future studies may use AMES to examine its relationships with athletes’ cognition, affect, and performance. The application of AMES in sport psychology was also discussed.